An analysis of the need to develop gamification-based teaching materials for Indonesian language learning in primary schools - Desmutri Hasanawati; Akbar Almasjid; Elyas Djufri (Rafandha Press, 2026)
Background: Indonesian language learning, particularly reading instruction, has not yet been implemented optimally and continues to face challenges in fostering students' interest in reading. Gamification is considered a promising approach to enhancing students' engagement and participation in the learning process. Purpose: This study aims to analyze teachers' needs for the development of gamification-based interactive digital teaching materials for Indonesian language learning in elementary schools. Method: This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with 10 Phase B (Grades 3–4) elementary school teachers in the Yogyakarta region. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. Findings: The findings indicate that: (1) Phase B students' interest in reading remains low; (2) teacher creativity plays a crucial role in creating an engaging learning environment; (3) teachers' understanding of gamification is generally limited to enjoyable classroom activities and does not comprehensively encompass its core elements; (4) limited knowledge, time constraints, and inadequate facilities hinder the implementation of gamification in learning; and (5) teachers need gamification-based interactive digital teaching materials that are varied, engaging, practical, effective, and accompanied by user guidelines.